Cross-Linguistic Dynamics: Adaptations in Translating English-Specific Structures into Kurdish - Muhammad, Kawa (Al-Adab Journal, 2026)
This study is about the dynamics of translating language-specific elements, which are conventionally labeled as the” untranslatable”, from a language into another. It specifically investigates the adaptation strategies used for translating certain compound adjectives specific to English with unique cognitive and cultural inferences into Kurdish. The aim of the investigation was to discover whether those English-specific structures are translated adaptively or creatively. The study was also an attempt to identify and categorize the translation patterns and strategies used in adapting the English compound adjectives in Kurdish. To achieve these aims, 20 Kurdish-speaking university instructors who specialize in teaching English as a foreign language were purposively selected as the study’s participants to fulfill the translation task. Having received relevant instructions regarding task objectives and the required translation method, the participants constructed their responses accordingly. The Kurdish translations were back-translated into English for facilitating and understanding the analysis. One of the outstanding findings of the study was that such English-specific structures can be handled differently in Kurdish language. This have resulted in the discovery of various adaptation strategies (or linguistic reconstruction patterns) not only for translating different examples, but also for the same example of the structure.